Vishaharayogas in Sahasrayoga: A review - Hussain, Gazala (Journal of Drug Delivery and Therapeutics, 2019)
Ayurveda pharmaceutics deals with preparation of medicines. The formulations are in different forms with a variety of ingredients that are herbal, mineral, marine, etc. in origin. These formulations, based on the ingredients and the forms are mentioned in different conditions including in the management of poisons. Sahasrayoga is a book that is a compilation of different formulations that are mentioned in various diseases. A review of this book has put light on the yogas that are mentioned in the management of various poisons. In this book, for the management of poisons different dosage forms are mentioned like kashaya, churna, leha, ghrita, etc. The formulations mentioned are not just for management of visha but are also indicated in other disorders. Keywords: Visha, Yogas, Vishaghna, Ayurveda, formulations